Pengaruh Tahfizul Quran Terhadap Perilaku Terpuji Siswa - Azis, Abdul (Mulya Literasi Publishing, 2022)
This study aims to find out whether there is a moral increase after students participate in the tahfidz program at SD IT Tadzkia Kota Langsa considering that morals are a very important part that must be owned by every human being in accordance with sharia guidance which is reviewed based on observations and interview results with teachers who have existed since the elementary school was established. This type of research is qualitative descriptive research, with primary data and secondary data. The data collection techniques used are observations, interviews, and documentation. The results of this study showed that the implementation of the tahfidz program at SD IT Tadzkia Kota Langsa was carried out in accordance with the syllabus and curriculum that had been established. The implementation of the tahfidz program at Tadzkia IT Elementary School every day is held at 07:30 which starts with doing gymnastics to increase the enthusiasm of students and also doing murojaah for 30 minutes and entering the classroom at 8:30 followed by tahfidz lessons until 10:30. The achievement of the target of the tahfidz program in elementary school has also been set, namely when the students of grades 1 to 3 when they want to memorize the teacher read the surah that wants to be memorized and then repeated by students until they are memorized, when the 4th grade the students are able to be independent in memorizing until finally when the 6th grade they will be laughed at' as many as 3 Juz by a special teacher (not a class teacher). The program was declared a success of up to 90% and made significant moral improvements.